Disease characteristics of HLA-B27 positive and negative finnish patients with juvenile idiopathic arthritis - results of the 18-year cohort follow-up study - Suvi Oili Orvokki Peltoniemi; Mia Glerup; Pekka Lahdenne; Kari K Eklund; Kristiina Aalto (BMC, 2023)
Abstract Background The aim of this long-term follow-up study was to compare the disease characteristics of HLA-B27 positive and negative patients with juvenile idiopathic arthritis (JIA). Methods The study is a cohort study with consecutive cases of newly diagnosed Finnish patients with JIA according to the International League of Associations for Rheumatology (ILAR) criteria [1]. Patients were enrolled between 1997 and 2000 from a defined area of Southern Finland. Clinical data including disease activity and serology were registered during a mean period of 17.5 years. Results 159 patients completed the 18-year follow-up study. HLA-B27 was available for 151 patients, of which 25% were HLA-B27 positive. Chronic uveitis was diagnosed in 30% of HLA-B27 positive and 29% of HLA-B27 negative patients. HLA-B27 positive patients had a lower prevalence of temporomandibular (TMJ) involvement than the antigen negative ones, 19% versus 28%. None of the HLA-B27 positive patients had cervical spine affected compared to 11% of antigen negative patients (p = 0.022). Of the HLA-B27 positive patients, 54% had had biological medication at some point during follow-up versus 25% in the negative group (p = 0.003). At last follow-up, 32% of antigen positive patients were not in remission compared to 18% of the antigen negative (p = 0.017). Conclusions The use of biological medication was more common in HLA-B27 positive patients with JIA. At the 18-year follow-up, more antigen positive patients had active disease compared HLA-B27 negative patients. This real-world follow-up study indicates that the prospects for worse outcome with HLA-B27 positivity in long-term should be taken into consideration.